A positive role for failure in virtue education. Issue 4 (2nd October 2017) - Athanassoulis, Nafsika
Abstract: This article outlines a role for constructive failures in virtue education. Some failures can be catastrophic and push the agent toward vice, but other types of failure can have positive consequences, we'll call these failures constructive failures, failures that help on the road to virtue. So, while failures are generally appealed to as examples of what to avoid doing, educators may want to actively create conditions that are likely to make their students fail. While failures may involve negative feelings in the short term, constructive failures, although they appear to pose obstacles in the learning process, actually help lead us to our goal, virtue. Crucially, constructive failures give us insights into situations and into ourselves, insights which make it more likely that we will succeed in the ultimate goal of virtue.